Complex approach to the prevention and treatment of progressive myopia in school children - Tarutta E.P; Iomdina E.N; Tarasova N.A.; Markosyan G.A.; Maksimova M.V. (РМЖ "Клиническая офтальмология")
Tarutta E.P., Iomdina E.N., Tarasova N.A., Markosyan G.A., Maksimova M.V. Moscow Research Institute of Eye Diseases named after Helmholtz Effective prevention of progressive myopia as a multifactorial ophthalmopathology requires a comprehensive approach, including various methods of targeted optical correction, functional stress and drug therapy. The review presents local and systemic drug support, improving the performance of the ciliary muscle and hemodynamics of the myopic eye, which have antioxidant and vasoconstrictor effects. The modern methods of targeted optical correction with the use of spectacles (with the creation of low-myopic defocus in the center and on the periphery of the retina), optical reflex methods, training exercises for ciliary muscle, various physical and hardware methods for affecting the motor and sensory components of the accommodation disorders of the myopic eye are described. The expediency of general physical activity, exercises and sports especially in the fresh air, but with the certain limitations associated with the individual state of the organ of vision, is shown. Modern approaches and the basic standards of complex treatment are reflected in the Federal recommendations «Clinical recommendation. Myopia «, available at http://avo-portal.ru. With the appointment of an adequate treatment complex, an individual approach is needed that takes into account the child’s health and the functional features of his organ of vision, which will stop the progression of myopia and prevent the development of irreversible pathological changes in the fundus of myopic genesis. Key words: myopia, functional treatment, anthocyanosides, accommodation, prophylaxis. For citation: Tarutta E.P., Iomdina E.N., Tarasova N.A. et al. Complex approach to the prevention and treatment of progressive myopia in school children. RMJ “Clinical ophthalmology”. 2018;2:70–76.